Optimization-Based Market-Clearing Procedure with EVs Aggregator Participation - López, Miguel Ángel; Aguado-Sánchez, José Antonio; De-la-Torre-Fazio, Sebastián Bienvenido; Figueroa, Miriam (My University, 2013)
For the upcoming new generation of electric power systems, i.e. smart grids, one of the most important challenges is to achieve an adequate economic and technical management involving the different agents in the process. In order to deliver the available power from suppliers to consumers, a market-clearing mechanism is needed. At the same time, technical operation calls for controlling that technical limits are not reached to preserve the security of the system. In this environment, Electric Vehicles (EVs) are gaining importance both in economic and technical issues. In this paper, an optimization-based approach is proposed for clearing the market in a smart grid. The traditional participants in energy markets are included in the formulation, stressing the role of EVs aggregators. The results presented in this paper illustrate the influence of EVs in the market-clearing procedure. The benefits for the system and EVs aggregators are also studied
Keywords: Optimización; Vehículos eléctricos; EVs aggregator; Market-clearing; Optimization